Updates on the taxonomy of Ilyobius nubilus (Navás, 1933) (Megaloptera: Sialidae: Sialinae) and Ilyobius brasiliensis (Navás, 1936) from southeastern Brazil - Mendes, Gabriela Caroline; Nascimento, Jeane Marcelle Cavalcante Do; Fusari, Lívia Maria; Hamada, Neusa (Zootaxa, 2024)
Species of the Neotropical genus Ilyobius Enderlein, 1910 (Megaloptera: Sialidae) are rare and poorly known because adults are infrequently collected in the field and the larvae have restricted habitat in the stream, facts that make obtaining specimens difficult to access for study. Herein we redescribe the female, describe the male and the larva of Ilyobius nubilus (Navás, 1933) based on specimens collected on the coast of São Paulo State. Adults were obtained mainly by rearing larvae in laboratory condition until adult emergence. The holotype for Ilyobius brasiliensis (Navás, 1936) was examined, and we contand that it is a valid species. Therefore, we do not corroborate its synonymy with I. nubilus. Ilyobius nubilus is a member of the I. chilensis group, and the male genitalia structure, described in this work, also supports its inclusion in this species group.